2021
DOI: 10.1002/adma.202104414
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic CsSnI3 for Efficient and Flexible Near‐Infrared Perovskite Light‐Emitting Diodes

Abstract: All‐inorganic and lead‐free CsSnI3 is emerging as one of the most promising candidates for near‐infrared perovskite light‐emitting diodes (NIR Pero‐LEDs), which find practical applications including facial recognition, biomedical apparatus, night vision camera, and Light Fidelity. However, in the CsSnI3‐based Pero‐LEDs, the holes injection is significantly higher than that of electrons, resulting in unbalanced charge injection, undesired exciton dissipation, and poor device performance. Herein, it is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 41 publications
2
77
0
Order By: Relevance
“…2020 red standard of (0.708, 0.292). 146 In another work, Lu et al 147 reported the flexible near-infrared tin-based CsSnI 3 PeLED. A dendritic CsSnI 3 perovskite structure was sandwiched between PEDOT:PSS and B3PyMPM as the hole and electron transport layers.…”
Section: Tin-based Perovskite Devicesmentioning
confidence: 99%
“…2020 red standard of (0.708, 0.292). 146 In another work, Lu et al 147 reported the flexible near-infrared tin-based CsSnI 3 PeLED. A dendritic CsSnI 3 perovskite structure was sandwiched between PEDOT:PSS and B3PyMPM as the hole and electron transport layers.…”
Section: Tin-based Perovskite Devicesmentioning
confidence: 99%
“…More importantly, the fabricated PeLEDs can also keep 93.4% of initial EQEs after 50‐cycle bends. [ 115 ] Thus, other environment‐friendly perovskites are also possible to form structures suitable for flexible application via readily controlling the concentrations of the precursor.…”
Section: Perspectivementioning
confidence: 99%
“…Lu et al successfully prepared the high-quality CsSnI 3 perovskite films with dendritic structure, which remained as fresh after 2000-cycle bends. More importantly, the fabricated PeLEDs can also keep 93.4% of initial EQEs after 50-cycle bends [115]. Thus, other environment-friendly perovskites are also possible to form structures suitable for flexible application via readily controlling the concentrations of the precursor.…”
mentioning
confidence: 99%
“…They found unbalanced charge injection, that the hole injection is higher than that of electron, was a cause of poor device performance. The dendritic structure remedied this by increasing electron injection, and the CsSnI 3 -based perovskite LEDs based on this structure obtained a record EQE of 5.4% with an acceptable efficiency roll-off and a high radiance of 162 W sr −1 m −2 ( Lu et al, 2021 ). However, the efficiency of Sn-based NIR-LEDs remains considerably lower than that of Pb-based devices owing to the rapid oxidation of Sn 2+ to Sn 4+ , which leads to poor device performance and accelerates degradation.…”
Section: Introductionmentioning
confidence: 99%